Ecological Critique of Modernity in the Qur’anic Perspective: Human Responsibility toward the Environment and Relevance to the SDGs - Yogi Sopian Haris; Lalu Rahmat Sugiara; Ahmad Fauzi; Lalu Muhammad Salikurrahman (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2025)
The increasingly concerning global ecological crisis, such as climate change, deforestation, environmentalpollution, and the rampant illegal mining, is a consequence of modernity that carries an anthropocentric paradigmand the irresponsible exploitation of natural resources. This research aims to critically examine the ecologicalimpacts of modernity and explore the Qur'anic perspective on human ecological responsibility, in relation to theSustainable Development Goals (SDGs). This research employs a library research method with a qualitativeapproach, through a literature study of Quranic exegesis sources, Islamic ecology literature, and SDG policydocuments. The findings indicate that the Quran explicitly criticizes human behavior that causes environmentaldamage, as stated in QS. Ar-Rum: 41, QS. Al-A’raf: 56, and QS. Al-Baqarah: 205, which depict humansdamaging the earth by destroying crops and livestock for personal gain. These verses emphasize that humanecological responsibility in Islam is spiritual and moral in nature, not merely technical. This perspective alignswith the sustainability values in the SDGs, such as illegal logging, unlicensed mining exploitation, and ecosystemdestruction, particularly SDG number 13 (Climate Action), which encourages concrete actions to address climatechange and its impacts, SDG number 14 (Life Below Water), which emphasizes the protection of marineecosystems from pollution and excessive exploitation, and SDG number 15 (Life on Land), which focuses on thepreservation of terrestrial ecosystems, sustainable forest management, and halting biodiversity loss. Theimplications of this research emphasize the need for the integration of Quranic values into environmental policiesand ecological education to build a development paradigm that is just, sustainable, and based on spirituality.